2014
DOI: 10.17795/gct-19169
|View full text |Cite
|
Sign up to set email alerts
|

R462Q Mutation in Prostate Cancer Specimens

Abstract: Background: A candidate gene for hereditary prostate cancer (PC), recently identified is the RNASEL gene on the chromosome loci 1q25. This gene mediates the apoptotic and antiviral activities of interferon. In some studies, a significant relationship has been reported between the chromosome 1q24-25 (HPC1) and prostate cancer risk, while some other studies did not approve. Objectives: The aim of this study was to determine the association between R462Q mutation and prostate cancer in a cross-sectional study. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We read with interest the article of Seidabadi et al titled "R462Q Mutation in Prostate Cancer Specimens" in the previous issue of "Gene, Cell and Tissue" (1). In this study, the authors reported that the genetic variant R426Q within the RNASEL gene is not associated with the risk of prostate cancer in a population from Iran.…”
Section: Dear Editormentioning
confidence: 91%
“…We read with interest the article of Seidabadi et al titled "R462Q Mutation in Prostate Cancer Specimens" in the previous issue of "Gene, Cell and Tissue" (1). In this study, the authors reported that the genetic variant R426Q within the RNASEL gene is not associated with the risk of prostate cancer in a population from Iran.…”
Section: Dear Editormentioning
confidence: 91%
“…In the previous issue of "Gene, Cell and Tissue", Seidabadi et al further elucidated the role of Arg462Gln mutation of RNASEL within a pathology databank (8). Sequencing of paraffin-embedded prostate cancer tissue was compared to benign prostate pathology.…”
Section: Dear Editormentioning
confidence: 99%
“…However, there are conflicting views regarding the role RNASEL in the etiology of sporadic prostate cancer. We read with interest the article of Seidabadi and colleagues "R462Q Mutation in Prostate Cancer Specimens" (5). The authors provide a clinicopathologic analysis to show the association between the RNASEL Arg462Gln polymorphism and prostate cancer (PC) risk.…”
Section: Dear Editormentioning
confidence: 99%